[tex]\displaystyle\bf\\1)\\\\3x^{7} \cdot(-2x^{3} )^{4} =3x^{7} \cdot(-2)^{4} \cdot(x^{3} )^{4} =3x^{7} \cdot16\cdot x^{12} =48x^{7+12} =48x^{19} \\\\\\2)\\\\\frac{4}{9} ab^{2} \cdot(-9a^{2} )^{3} b=\frac{4}{9} ab^{2} \cdot(-9)^{3} \cdot(a^{2} )^{3} \cdot b=\frac{4}{9} ab^{2}\cdot( -729)\cdot a^{6} \cdot b=\\\\=-\frac{4}{81} a^{1+6} b^{2+1} =-\frac{4}{81} a^{7} b^{3}[/tex]
Объяснение:
А)
3х⁷ * (-2х³)⁴ = 3х⁷ * (-2)⁴ * (х³)⁴ =
3х⁷ * 16 * х¹² = (3 * 16) * (х⁷ * х¹²) =
48 * х¹⁹ = 48х¹⁹
Б)
4/9аb² * (-9a²)³b = 4/9ab² * (-9)³ * (a²)³ * b =
4/9ab² * (-729) * a⁶ * b =
(4/9 * (-729)) * (a * a⁶) * (b² * b) =
(4/1 * (-81)) * a⁷ * b³ = -324 * a⁷ * b³ = -324a⁷b³
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
[tex]\displaystyle\bf\\1)\\\\3x^{7} \cdot(-2x^{3} )^{4} =3x^{7} \cdot(-2)^{4} \cdot(x^{3} )^{4} =3x^{7} \cdot16\cdot x^{12} =48x^{7+12} =48x^{19} \\\\\\2)\\\\\frac{4}{9} ab^{2} \cdot(-9a^{2} )^{3} b=\frac{4}{9} ab^{2} \cdot(-9)^{3} \cdot(a^{2} )^{3} \cdot b=\frac{4}{9} ab^{2}\cdot( -729)\cdot a^{6} \cdot b=\\\\=-\frac{4}{81} a^{1+6} b^{2+1} =-\frac{4}{81} a^{7} b^{3}[/tex]
Verified answer
Объяснение:
А)
3х⁷ * (-2х³)⁴ = 3х⁷ * (-2)⁴ * (х³)⁴ =
3х⁷ * 16 * х¹² = (3 * 16) * (х⁷ * х¹²) =
48 * х¹⁹ = 48х¹⁹
Б)
4/9аb² * (-9a²)³b = 4/9ab² * (-9)³ * (a²)³ * b =
4/9ab² * (-729) * a⁶ * b =
(4/9 * (-729)) * (a * a⁶) * (b² * b) =
(4/1 * (-81)) * a⁷ * b³ = -324 * a⁷ * b³ = -324a⁷b³